Analysis of Bragg fiber waveguides having a defect layer for biosensing application - Chourasia, Ritesh Kumar; Yadav, Chandan Singh; Upadhyay, Abhishek; Chourasia, Nitesh Kumar; Singh, Vivek (Elsevier GmbH, 2020)
A novel hollow core Bragg fiber waveguides having a defect layer are proposed and analyzed theoretically for sensing application. Matching the electric and magnetic fields at various interfaces, a relation between fields of first layer with final layer has been stabilized; hence, the equations for reflectance and transmittance of proposed structure are derived. Due to periodicity of concentric cylindrical structure, a perfect photonic band gap is observed in considered wavelength range. The presence of defect layer in cylindrical periodic structure shows a peak corresponding to defect mode in perfect photonic band gap region. The full width at half maxima of this peak depends on the periodicity of the cladding layers. Also, the spectral position and shift of peak of defect mode depend on the angle of incidence of light, refractive index of core material and design wavelength of structure. Therefore, it is more appropriate to consider this peak of defect mode as sensing signal instead of considering whole photonic band gap as sensing signal.
Keywords: Bragg fiber waveguide; Defect mode; High and low contrast cladding; Sensitivity; Transfer matrix method